SP1 promotes triple-negative breast cancer progression by targeting USP5 - Shi-Yi Wu; Zi-Mei Peng; Feng-Yi Deng; Jin-Yong Xiong; Pu-Ying Luo; Xiao-Jian Han; Zhen Zhang (Cancer Cell International)
Abstract Background Triple-negative breast cancer (TNBC) is characterized by the absence of targeted therapies and a dismal prognosis, necessitating a critical exploration of the molecular mechanisms driving TNBC pathogenesis and the identification of novel therapeutic targets. While dysregulated USP5 expression has been observed in various malignancies, its specific functions and mechanisms in TNBC remain poorly understood. Methods The study utilized a combination of TCGA database analysis, immunohistochemistry staining (IHC), quantitative RT-PCR, and western blotting assay to investigate the expression of USP5 and SP1 in TNBC. Furthermore, the study examined the role of the SP1-USP5 axis and the USP5 inhibitor periplocin in TNBC progression through CCK-8 assay, colony formation assay, EDU incorporation assay, and tumor xenograft experiments. Additionally, the study explored the underlying mechanisms involved in the regulation of USP5 expression in TNBC using luciferase assay, ChIP-qPCR, quantitative RT-PCR, and western blotting assay. In order to ascertain potential inhibitors of USP5 activity, a combination of the Molecular Operating Environment (MOE) multi-functional docking platform, cellular thermal shift assay, and in vitro USP5 activity assay were utilized. Results In the current investigation, it was observed that the expression of USP5 was elevated in TNBC and was significantly correlated with decreased overall survival rates among patients. The upregulation of USP5 was found to be mediated by the transcription factor SP1 through its binding to the USP5 promoter, consequently facilitating the progression of TNBC. Notably, the natural compound periplocin was identified as a promising inhibitor of USP5, demonstrating potential efficacy in impeding the advancement of TNBC. Conclusions Our research findings indicate that the SP1-USP5 signaling pathway is significantly involved in the advancement of TNBC, and periplocin’s ability to target USP5 presents a potential therapeutic approach for managing TNBC. These results offer valuable insights for the development of novel treatment strategies for TNBC patients.